Functioning of Adults from Single-Parent Families in a Family and Professional Environment - Wojciechowska, Mariola; Michalska, Marlena (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The modern world puts great demands on people when it comes to understanding its purpose and meaning, which undoubtedly changes the lives of individuals and social groups. People are particularly concerned about the possibility of freeing themselves from imposed group ties, enjoying the rights of a citizen and a member of a community, and the way in which freedom is exercised without restrictions. What has so far been a well-established basis for human activity and the maintenance of the existing order is now losing its importance, and is being replaced by new life opportunities. The authority of traditional social structures such as the social class, local community or family has declined. Normative and axiological systems, and consequently the quality of functioning of the contemporary family, its structure, scope of performed duties and relations within a family, have also undergone transformations. It is becoming increasingly common for adults who form the main axis of the family to decide on a divorce. This is not conducive to the optimum development of children, as they lose the sense of security, trust in adults, fail to fulfil their own lives and even doubt about the existence of true unselfish love. Parents' divorce decisions often result in emotional and motivational disorders which are manifested by difficulties in establishing social contacts, building profound relationships and coping with difficult situations. The paper shows the results of exploratory research on how adults brought up in divorced single-parent families can function in the social and professional environment. The research employs the diagnostic survey method using the auditorium questionnaire and the “100 Sentences – 100 Opinions” tool by Mirosław J. Szymański. The results of the research clearly show that adults brought up in single-parent families are involved very differently in social and professional life. They build their short- and long-term professional and personal goals in distinct ways. Personal and social characteristics of the respondents are the factors determining the observed activity. The research results are in line with the relevant literature and prove the impact of growing up in a single-parent family on children's activity in adult life.